Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/jnr.24217
|View full text |Cite
|
Sign up to set email alerts
|

Cross multivariate correlation coefficients as screening tool for analysis of concurrent EEG‐fMRI recordings

Abstract: Over the past decade, the simultaneous recording of electroencephalogram (EEG) and functional magnetic resonance imaging (fMRI) data has garnered growing interest because it may provide an avenue towards combining the strengths of both imaging modalities. Given their pronounced differences in temporal and spatial statistics, the combination of EEG and fMRI data is however methodologically challenging. Here, we propose a novel screening approach that relies on a Cross Multivariate Correlation Coefficient (xMCC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
2
5
0
Order By: Relevance
“…In conclusion, the present study demonstrated that FSS, in conjunction with a multivariate correlation and feature selection approach proposed previously (Ji et al, 2018), yields robust ssVEP-fMRI co-variation maps with high face validity (i.e., high correspondence between BOLD and ssVEP in visual cortex, where strong responses are expected to during visual stimulation) and with high replicability across re-tests (i.e., across three experimental phases) in the same participants. The work is important to neurorobotics for several reasons: (1) This approach could be used to examine a wide range of hypotheses regarding the neurophysiology of visual cortex and its function for biological and artificial systems, (2) it provides a means to conduct the multi-modal information fusion and correlation analysis to recover the underlying neurophysiological mechanisms, and (3) the core idea of the approach are inspiring for other brain data processing and the knowledge can be transferred to other applications as well.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…In conclusion, the present study demonstrated that FSS, in conjunction with a multivariate correlation and feature selection approach proposed previously (Ji et al, 2018), yields robust ssVEP-fMRI co-variation maps with high face validity (i.e., high correspondence between BOLD and ssVEP in visual cortex, where strong responses are expected to during visual stimulation) and with high replicability across re-tests (i.e., across three experimental phases) in the same participants. The work is important to neurorobotics for several reasons: (1) This approach could be used to examine a wide range of hypotheses regarding the neurophysiology of visual cortex and its function for biological and artificial systems, (2) it provides a means to conduct the multi-modal information fusion and correlation analysis to recover the underlying neurophysiological mechanisms, and (3) the core idea of the approach are inspiring for other brain data processing and the knowledge can be transferred to other applications as well.…”
Section: Discussionsupporting
confidence: 75%
“…This is consistent with the sources of ssVEP established through intracranial recordings in humans and experimental animals (see e.g., Wittevrongel et al, 2018). Furthermore, the cross-participant and re-test convergence along with the large spatial extent of the ssVEP-fMRI covariation in visual cortex observed in the present study exceeds earlier analyses of this same data-set with different methods, i.e., parametric modulation analysis as implemented in SPM (Petro et al, 2017), and multivariate correlation analyses without the FSS preprocessing step (Ji et al, 2018). Because the covariation of both signal modalities across the time series in visual cortex can be considered a gold standard for analytical strategies, the fact that ssVEP-fMRI correlations were observed reliably in extended visual cortex suggests that FSS represents a desirable preprocessing step, positively affecting the validity of EEG-fMRI fusion.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations